Prognostication after cardiac arrest: Results of an international, multi-professional survey. (May 2019) - Steinberg, Alexis; Callaway, Clifton W.; Arnold, Robert M.; Cronberg, Tobias; Naito, Hiromichi; Dadon, Koral; Chae, Minjung Kathy; Elmer, Jonathan
Abstract: Aim: We explored preferences for prognostic test performance characteristics and error tolerance in decisions regarding withdrawal or continuation of life-sustaining therapy (LST) after cardiac arrest in a diverse cohort of medical providers. Methodology: We distributed a survey through professional societies and research networks. We asked demographic characteristics, preferences for prognostic test performance characteristics and views on acceptable false positive rates for decisions about LST after cardiac arrest. Results: Overall, 640 respondents participated in our survey. Most respondents were attending physicians (74%) with >10 years of experience (59%) and practiced at academic centers (77%). Common specialties were neurology (22%), neuro- or general critical care (24%) and palliative care (31%). The majority (56%) felt an acceptable FPR for withdrawal of LST from patients who might otherwise have recovered was ≤0.1%. Acceptable FPRs for continuing LST in patients with unrecognized irrecoverable injury was higher, with 59% choosing a threshold ≤1%. Compared to providers with >10 years of experience, those with <5 years thought lower FPRs were acceptable (P < 0.001 for both). Palliative care providers accepted significantly higher FPRs for withdrawal of LST (P < 0.0001), and critical care providers accepted significantly higher FPRs for provision of long-term LST (P = 0.02). With regard to test performance characteristics, providers favored accuracy over timeliness, and prefer tests be optimized to predictrather than favorable outcomes. Conclusion: Medical providers are comfortable with low acceptable FPR for withdrawal (≤0.1%) and continuation (≤1%) of LST after cardiac arrest. These FPRs may be lower than can be achieved with current prognostic modalities.